Enamel subsurface remineralization potential of virgin coconut oil, coconut milk and coconut water - Rahamat, Siti Fatimah; Wan Abd Manan, Wan Nor Hayati; Jalaludin, Anil Azura; Abllah, Zurainie (Elsevier, 2019)
Dental caries occurred due to acidic attack to the enamel tooth surface causing loss of minerals. Remineralization reversed the effect provided high calcium and phosphorus are presence in the oral environment. This study aims to investigate the potential of VCO, coconut milk, and coconut water in remineralization of enamel subsurface. The study uses SEM/EDX to evaluate the changes of calcium and phosphorus on the enamel subsurface before and after treatment. An overall comparison of the treatments using one-way ANOVA showed a significant difference with p < 0.05. The VCO, coconut milk, and coconut water are potentially capable for enamel remineralization.